Labor market sorting on personality traits and the gender wage gap. Issue 11 (24th June 2020) - Lesner, Rune V.
ABSTRACT: Gender sorting in the labor market can explain a major part of the gender wage gap. This paper documents the association between the gender wage gap and labor market sorting into jobs characterized by their requirements to personality traits. Two thirds of the Danish gender wage gap from 2008 to 2015 explained by occupational sorting can be explained by characterizing occupations by their requirements to personality traits. This amounts to around a quarter of the gender wage gap explained by these nonpecuniary occupational characteristics. In particular, men are awarded for working in jobs that require higher levels of disagreeableness